Data scopes for digital history research. Issue 2 (3rd April 2019) - Hoekstra, Rik; Koolen, Marijn
Abstract: The term Macroscope has recently been introduced as an instrument to study historical big data using digital tools. In this paper we argue the need for a more elaborate set of concepts to describe and reason about the interactions to select, enrich, connect, analyse and evaluate historical data using digital tools. Interactions change the data and are essential in understanding any subsequent analysis. It makes them part of historical research methodology, but there is little consensus on how these steps can or should be performed. Moreover, they are rarely reported and discussed. We introduce the term data scope as an instrument encompassing these choices and interactions. Elaborating on these processes encourages deeper reflection on and discussion of the interactions and their consequences for research outcomes.